THE ANALYSIS OF STUDENTS' PREPAREDNESS FOR THE SUBJECT "CONSTRUCTIONAL MACHINE ELEMENTS" TAUGHT AT THE FACULTY OF ENGINEERING - KADNAR, Jozef; KADNAR, Milan (Trends in education, 2010)
The aim of the article is to analyse the students' preparedness for the subject "Constructional Machine Elements" which is taught at the Faculty of Engineering, Slovak University of Agriculture in Nitra. Based on a questionnaire, the main aim is to evaluate the students' preparedness for the subject.
Keywords: questionnaire; students' preparedness; Constructional Machine Elements.